Stages of Change Scale to Measure Work Readiness of Transition-Age Youth With Disabilities: A Promising Approach. (October 2021) - Schlegelmilch, Amanda; Roskowski, Matthew; Brinck, Emily A.; Anderson, Catherine A.; Hartman, Ellie; Chan, Fong; Tansey, Timothy N.; Decker-Maurer, Heidi
The experience of transitioning into adulthood is a critical phase in life. The navigation of government benefits adds further complexity that can affect employment outcomes for youth with disabilities. Some individuals hesitate to work out of fear to losing access to monetary, disability, and related health care benefits. However, using available work incentives while pursuing employment and career paths can provide opportunities to work and address poverty without forgoing needed services. The Wisconsin Promoting Readiness of Minors in Supplemental Security Income (PROMISE) research grant aimed to positively change youth readiness to work through the use of Motivational Interviewing, work incentive benefits counseling, financial capability building, shifting expectations, and help in navigating transition resources. To measure the impact on readiness to work, 126 transition-age youth receiving supplemental security income (SSI), 188 of their family members, and 411 Division of Vocational Rehabilitation (DVR) counselors working with the youth and families completed a modified Stages of Change Scale survey. Results indicated that youths' work readiness and positive feelings about work significantly increased from baseline to follow-up, along with an increase in employment rates. The implications of these findings highlight the utility of incorporating the stages of change theory into the design and implementation of services and supports to increase work readiness for youth with disabilities in transition.